2020
DOI: 10.1016/j.lungcan.2020.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and the role of bronchoscopic intervention in patients with primary pulmonary salivary gland-type tumors

Abstract: Primary pulmonary salivary gland-type tumors (PSGT) are rare among all types of lung cancer. The purpose of this study was not only to evaluate the clinical outcomes and prognostic factors after treatment, but also to assess the role for bronchoscopic intervention in PSGT. Methods: We analyzed the medical data of 181 PSGT patients who were treated between 1995 and 2018. Patients were divided into three groups according to the initial treatment, as follows: surgical resection with/ without adjuvant therapy incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Important prognostic factors of MEC include age, TNM stage and pathological differentiation grade ( 21 23 ). Poor OS was associated with older age, higher clinical stages, larger tumour size and non-surgical treatments ( 24 26 ). Our study found that the survival of PMEC patients was not only significantly affected by factors of age, pathological differentiation, TNM stage, tumor size, lymph node metastasis, distant metastasis and treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Important prognostic factors of MEC include age, TNM stage and pathological differentiation grade ( 21 23 ). Poor OS was associated with older age, higher clinical stages, larger tumour size and non-surgical treatments ( 24 26 ). Our study found that the survival of PMEC patients was not only significantly affected by factors of age, pathological differentiation, TNM stage, tumor size, lymph node metastasis, distant metastasis and treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy or chemotherapy can be added to the treatment depending on the presence of residual tumor at the resection margin 8,9 . A multidisciplinary approach to the management of ACC involving IP, oncology and thoracic surgery clinics would be beneficial in terms of patient survival and quality of life 10,11 . IBPs are a palliative treatment option in patients who are not surgical candidates or in cases of recurrence following surgical resection, oncologic treatment or previous IBPs 3,6,11 .…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach to the management of ACC involving IP, oncology and thoracic surgery clinics would be beneficial in terms of patient survival and quality of life 10,11 . IBPs are a palliative treatment option in patients who are not surgical candidates or in cases of recurrence following surgical resection, oncologic treatment or previous IBPs 3,6,11 . Indeed, we found that IBP contributes to the palliative treatment of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations